Insights into the aetiology of snoring from observational and genetic investigations in the UK Biobank - Adrián I. Campos (Nature Portfolio, 2020)
Snoring is common in the population and tends to be more prevalent in older and/or male individuals. Here, the authors perform GWAS for habitual snoring, identify 41 genomic loci and explore potential causal relationships with anthropometric and cardiometabolic disease traits.